THE SIGNIFICANCE OF AUTHENTIC TEXTS AT RUSSIAN LESSONS IN COMPREHENSIVE SCHOOLS - Nizomitdinova Zulaikho Abduazizovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article deals with issues related to the methodology of teaching the Russian language in the national groups of the general education school.